2009
DOI: 10.1021/jp8075063
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensionally Ordered Macroporous ZrO2:Eu3+: Photonic Band Effect and Local Environments

Abstract: Three-dimensionally ordered macroporous (3DOM) ZrO 2 :Eu 3+ inverse opal materials prepared by polystyrene (PS) colloidal crystal templating, using the sol-gel method, were successfully fabricated. Their crystal structure, morphology, and photoluminescence (PL) properties and the effect of the photonic stop-band on the spontaneous emission of Eu 3+ ions were studied and compared with those of the nonporous sample. In the 3DOM ZrO 2 : Eu 3+ , significant suppression for the 5 D 0 -7 F 1 transition peaking at 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 31 publications
(66 reference statements)
1
44
0
Order By: Relevance
“…As is well known, in the NCs, surface defects such as broken bonds/dangling bonds and a large number of surface adsorptions such as OH-and CO 2 bonds are generally involved. The surface defects may quickly trap the energy from both by excited Ce 3 + prior to energy transfer and excited levels of Tb 3 + nonradiatively; such surface adsorption groups have large phonon energy and can act as nonradiative relaxation channels to bridge the emitting levels of Tb 3 + and the ground states, both giving rise to an increase of nonradiative transition rate [43]. As stated above, samples S1-4 are synthesized with different condition and therefore exhibit different morphology and size.…”
Section: Pl Decay Dynamicsmentioning
confidence: 99%
“…As is well known, in the NCs, surface defects such as broken bonds/dangling bonds and a large number of surface adsorptions such as OH-and CO 2 bonds are generally involved. The surface defects may quickly trap the energy from both by excited Ce 3 + prior to energy transfer and excited levels of Tb 3 + nonradiatively; such surface adsorption groups have large phonon energy and can act as nonradiative relaxation channels to bridge the emitting levels of Tb 3 + and the ground states, both giving rise to an increase of nonradiative transition rate [43]. As stated above, samples S1-4 are synthesized with different condition and therefore exhibit different morphology and size.…”
Section: Pl Decay Dynamicsmentioning
confidence: 99%
“…3,8 This feature can be exploited to control the spontaneous emission of an embedded light emitter in PhCs by manipulating the local photonic density of state. Several studies have been undertaken on the nature of spontaneous emission of semiconductors quantum dots [9][10][11] , organic dyes [12][13][14] and rare-earth ions [15][16][17][18][19][20] containing PhCs. In recent years, immense interest has aroused in (i) complex PhCs, produced by introduction of crystal defects (such as point, 8,[21][22] line, [23][24][25] or planar [26][27] ) and (ii) photonic crystal heterostructures [28][29][30] (termed as PhCHs) due to their potential in improving ultra-high quality nanocavity and light harvesting efficiency besides developing quality optical filters.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations undertaken earlier focused on the modification of lanthanide ions emission with PhCs possessing a single PSB. 15,19,[52][53] Note that lanthanide ions exhibit several emissions (e.g., 488, 545, 580, and 625 nm for Tb 3+ species) and hence a 5 single PSB cannot possibly suppress (i) bands existing on both sides of a desired emission (545 nm) and/or (ii) two or more distant bands simultaneously. 52,[54][55] The present work addresses this issue and deals with the spontaneous emission aspect of Tb 3+ ion embedded in silica IOH, exhibiting two PSBs with one PB in between, vis-à-vis IOs using SiO 2 : Tb 3+ powder as reference.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained meso-and macroporous architectures can be useful in applications where large surface areas are to be preserved during high temperature operations as, for instance, in heterogeneous catalysis. Several experimental studies have been reported on the successful formation of the macroporous photonic crystals of zirconia, ceriazirconia and rare-earth doped zirconia and the modification of spontaneous emission of the embedded luminescent species in the photonic crystals [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, luminescence studies can provide important information about intrinsic and impurity defects in pure and doped ZrO 2 [17][18]. The techniques employed to study the optical properties of lanthanide ion-doped ZrO 2 materials include cathodoluminescence [12,[18][19][20], photoluminescence [13][14][15][16][21][22][23][24][25][26][27] and thermoluminescence [12,[28][29][30][31][32] spectroscopies. Light emission from rare-earth ions is mainly due to electric and magnetic dipole optical transitions within the 4f manifolds or involving configurations such as 4f nÀ 1 and 5d [17].…”
Section: Introductionmentioning
confidence: 99%